Feasibility study of recycled tire powder in construction blocks cement to decrease environmental pollution (a case study: Ahvaz, Iran) - Eslami, Mohsen; Raof, Farzaneh Fakeri; Zadeh, Mohammad Jorjor (Ciência e Natura, 2015)
Today, retrieval and optimal use of exiting recourses and environmental protection is in view of seriousattention of the development in the world. Approximately 300 thousand tons of old tires in the country hascaused environmental pollution. Recycling of waste tires is completely different to which is done in our country.Unfortunately recycling scrap tires has not favorable growth in our country. Millions of tires are discarded eachyear, and the scrap piles of rubber this creates pose serious environmental problems. Rubber tires also leachhazardous materials into the environment as they decompose. This study was performed in Ahvaz metropolitan.In this study there are 9 building blocks which had different percentages of rubber powder as filling materials.Pressure test done on these blocks. The result of the stress test on the samples compared with the result of thestress test on the main samples. The comparison showed that by adding 10% of rubber powder instead of fillermaterial in the process of preparing the block, there was no change in compressive strength. Therefore this blockwill be replaced by blocks used in construction industry. At least some of the environmental hazards caused byincorrect tire were buried as were recommendation to improve.